An experimental and numerical investigation of heat transfer enhancement for graphene nanoplatelets nanofluids in turbulent flow conditions. (February 2015) - Sadeghinezhad, Emad; Togun, Hussein; Mehrali, Mohammad; Sadeghi Nejad, Parvaneh; Tahan Latibari, Sara; Abdulrazzaq, Tuqa; Kazi, S.N.; Metselaar, Hendrik Simon Cornelis
Abstract: In this paper, both experimental and numerical studies have been performed on the turbulent heat transfer of the graphene nanoplatelets nanofluids in a horizontal stainless steel tube that was subjected to a uniform heat flux at its outer surface. An experimental investigation was done to evaluate the heat transfer characteristics and the pressure drop of a graphene nanoplatelet (GNP) nanofluid and in numerical study, the finite volume method with standard k – ɛ turbulence model is employed to solve the continuity, momentum, energy and turbulence equations in three dimensional domains. The thermal conductivity and viscosity of the GNP nanofluids at concentrations of 0.025, 0.05, 0.075, and 0.1 wt% were measured prior to the heat transfer experiments. The heat transfer and the pressure drop within the flowing base fluid (distilled water) were measured and compared with the corresponding data from the correlations and numerical study. The data were satisfied within a 5% error and 2% error for the numerical work. The effects of the nanoparticle concentration and the heat flux on the enhancement of the heat transfer turbulent flow condition are presented. The Nusselt number (Nu) of the GNP nanofluid was higher than the base fluid by approximately 3–83% and increased as the flow rate and the heat flux increased. However, the increase in the pressure drop ranged from 0.4% to 14.6%. Finally, the results reveals that the GNP nanofluids could function as a good and alternative conventional working fluid in heat transfer applications.